An industrial quality control study on Goodrich Manufacturing Corporation - Ambida, Julie-Ann O.; Edolsa, Charlene; Malabuyok, Annabelle (Diliman, Quezon City College of Engineering, 2005)
Goodrich Manufacturing Corporation is one of the major manufacturers of rubber slippers in the country. Being a manufacturing company, quality is of utmost importance to the management and their Quality Assurance Department ensures that all items for shipment would meet the company's standards and the customers' requirements. However, there would always be room for improvement in a production setting and despite the company's efforts, some quality problems are still encountered. As such, a quality control study was performed on the company to help address quality-related issues. Employing problem analysis tools such as the Ishikawa Diagram and the Pareto Chart, the group was able to come up with three defect classifications : for Rework, downgraded or Class B and Scrap; and three process non-conformities that contribute significantly to the mentioned defects : Off-cut in the cutting die, Missing buttons from strap curing and Overthickness in the calendering. The causes of the abovementioned non-conformities were found to be inadequate equipment maintenance and operator error. Upon doing Statistical Process Control, it was found out that the cutting process was out of control based on the np-charts. The data exhibited 9 points in a row in Zone C of the x-chart, which indicates a shift in the process average. The out-of-control situation is attributed to shift work because these data points occurred during the night shift, probably because of poor lighting conditions and decreased worker attentiveness. The x-chart for machine 3 signaled an out-of-control process due to a shift in the process mean. This was attributed to the fact that machine 3 is more prone to breakdown and failure due to old age. The data from the calendering process was first subjected to tests for normality after which a variables control chart was constructed for the data points. It indicated that the process was in control. The Process Capability Index for the calendering process was computed to be 0.2495 which means that the process is incapable of producing within the specifications set by the company. As for the third critical non-conformity, missing buttons, an np-chart was constructed for each of the three strap-curing machines. As the company presently employs no definite sampling plan, the group suggests varying sampling plans for incoming raw materials because of the shifting lot sizes. Yield Losses were calculated to be approximately P1.3 M a year. Because the group recommended incentives as a means for motivating the employees and also that the whole organization be oriented with SPC, potential savings from these would offset yield losses and benefit the company in the long run.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Goodrich Manufacturing Corporation; Footwear industry; Quality control